2018
DOI: 10.1186/s12891-018-2038-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the stem cell characteristics of murine tenocytes and tendon-derived stem cells

Abstract: Tendon is a commonly injured soft musculoskeletal tissue, however, poor healing potential and ineffective treatment strategies result in persistent injuries and tissue that is unable to perform its normal physiological function. The identification of a stem cell population within tendon tissue holds therapeutic potential for treatment of tendon injuries. This study aimed, for the first time, to characterise and compare tenocyte and tendon-derived stem cell (TDSC) populations in murine tendon. Tenocytes and TDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 43 publications
0
34
0
Order By: Relevance
“…Some studies have shown that cyclic tensile strain in vitro results in upregulation of proliferation and tenogenic differentiation of TDSCs 9,39 . Furthermore, TDSCs also have the potential for trilineage differentiation (osteogenesis, chondrogenesis and adipogenesis), and this capacity can be enhanced by adequate mechanical stimulation 17,30,33 . We showed that TDSCs isolated from the tendons with Botox injection into associated muscles display reduced proliferation, colony formation capacity and trilineage differentiation capacity (osteogenesis, chondrogenesis and adipogenesis).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that cyclic tensile strain in vitro results in upregulation of proliferation and tenogenic differentiation of TDSCs 9,39 . Furthermore, TDSCs also have the potential for trilineage differentiation (osteogenesis, chondrogenesis and adipogenesis), and this capacity can be enhanced by adequate mechanical stimulation 17,30,33 . We showed that TDSCs isolated from the tendons with Botox injection into associated muscles display reduced proliferation, colony formation capacity and trilineage differentiation capacity (osteogenesis, chondrogenesis and adipogenesis).…”
Section: Discussionmentioning
confidence: 99%
“…TDSCs are multipotent progenitor cells capable of differentiating into tendon, cartilage, bone and adipose tissue 17,38 . Therefore, we determined if injection of Botox into quadriceps muscle affected the multilineage differentiation potential of TDSC.…”
Section: Intramuscular Botox Injection Impairs the Viability And Diffmentioning
confidence: 99%
“…Self-reported demographics were collected by questionnaire, and for the Dupuytren's patients disease stage information was collected from clinical records. Equine superficial digital flexor tendon (SDFT) and healthy canine cranial cruciate ligament (CCL) were collected as described (Ali et al, 2018;Lee et al, 2018), with local ethical approval (VREC186, VREC62 and RETH00000553). Ruptured CCL, otherwise discarded as clinical waste, was obtained from dogs undergoing stifle/knee stabilisation at the University of Liverpool's Small Animal Teaching Hospital (VREC63).…”
Section: Sample Collectionmentioning
confidence: 99%
“…TDSCs are multipotent progenitor cells capable of differentiating into tendon, cartilage, bone and adipose tissue 17,39 . Therefore, we determined if injection of Botox into quadriceps muscle affects the multilineage differentiation potential of TDSC.…”
Section: Intramuscular Botox Injection Impairs the Growth And Differementioning
confidence: 99%